Hubungan antara Sikap dengan Perilaku Ibu Hamil tentang Pemeriksaan HIV/AIDS di Puskesmas Purwokerto Selatan - Shara Dhianing Gusti; Etika Dewi Cahyaningrum; Siti Haniyah (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Human Immunodeficiency Virus (HIV) is an infection that attacks white blood cells and weakens the body's immune system. Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms due to the weakening of the body's immune system due to HIV. The behavior of pregnant women who are willing to carry out HIV testing is influenced by the attitude of pregnant women, where there is an attitude of support for carrying out HIV testing by the pregnant women themselves. The purpose of this study was to determine the relationship between attitudes and behavior of pregnant women regarding HIV/AIDS testing at the South Purwokerto Health Center. Correlation study research design and cross-sectional time approach. The sample in this study were pregnant women who carried out examinations at the South Purwokerto Health Center, namely as many as 64 respondents using the accidental sampling technique. Data analysis was determined by chi-square test. The results showed that 39 respondents (60.9%) had a good attitude towards pregnant women. The behavior of the mother through HIV/AIDS examination was 43 respondents (67.2%). Based on the chi-square statistical test, it was found that it was 0.000<0.05, which means that there is a correlation between the attitudes of pregnant women and behavior regarding HIV/AIDS testing.